EVALUASI PERUBAHAN TEMPERATUR, pH DAN KELEMBABAN MEDIA PADA PEMBUATAN VERMIKOMPOS DARI CAMPURAN JERAMI PADI DAN KOTORAN SAPI MENGGUNAKAN LUMBRICUS RUBELLUS - Kusumawati, Nita (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
The purpose of this activity is to evaluate the changes in temperature, pH, and moisture mixed media during the composting process of rice straw and cow manure using earthworms Lumbricus rubellus as bioactivator. Vermi- compos is carried out by making a mixture consisting of 0%, 25%, 50%, 75% and 100% of waste rice straw in cow dung. The media is inserted into a plastic container and then fermented. In every 250 grams of fermented media is insert- ed as much as 250 grams of earthworms (Lumbricus rubellus) aged 2 months. During the composting process, regular measurement of temperature and pH of the media was doing. At the end of composting with earthworms, temperature is lowest at 26-28.6 ºC, there are  0% -25% of rice straw in cow dung. While the temperature of the media without earthworms lowest in the range of 26.8-29,3 ºC, there are 0% -25% of rice straw in cow dung. Media acidity during the composting process was almost the same for media without earthworm and with earthworms. Humidity highest during the composting process with earth- worms is around the 50.17 to 65.48% (0% rice straw), while the highest media moisture during the composting process without earthworms ranged from 50.07 to 64.36% (0% rice straw) (100% rice straw)